Evil and Islamic Theodicy (American Journal of Islam and Society, 2010)
On 12 January 2010, the world witnessed the complete devastation of Haiti, thishemisphere’s first black independent nation. That this is evil in its nature is disputedby none (Plato uses evil to refer to poverty, disease, pain, sickness, harm, injustice,badness, discord, chaos, disorder, ugliness, weakness, deformity, and other things).1What is deliberated, however, are the causes, effects, and what to do next. Moreappropriately, the international community rallied to help the innocent and helplessHaitians instead of trying to justify why this particular earthquake occurred. In thiseditorial, I seek to provoke philosophical debate and refocus theological attention onevil in the world, while hoping to raise more pointed questions about those whoattempted to provide absolute answers for this particular earthquake.The very next day, the infamous televangelist Pat Robertson of the “700 Club”dared to offer an apparent justification and cause of this earthquake.2 Much has beenstated about his insensitivity and the fabricated story he cited. But the absurdity of hisargument and the underlying ideology are even more troubling. He concluded thatGod was punishing the Haitians because their ancestors had made a “pact with theDevil” to help them gain independence from France. Thus, God has cursed all generationsof Haitians.Setting aside his lack of consideration of how this pact could have been made,the underlying conclusion is that the Haitians’ ancestors abandoned God in favor ofthe Devil (who had become effective in their quest for independence) and since thenGod has been taking revenge upon them, even on those citizens who follow otherreligions and thus have nothing to do with that alleged sin, either then or now. Whatdoes that say about God and His omnipotence and justice? Philosophers and theologianshave long struggled with these questions ...